Absolute poverty lines - Channing Arndt; Kristi Mahrt; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Private consumption capabilities form only one facet of comprehensive living standards assessments, but they are an important facet whose measurement should be done well. Measurement is complex due to a multitude of methodological choices, which often interact with imperfect data and a desire for comparability through time. This paper outlines ideas underpinning these choices with particular attention to the tensions between consistency and specificity. We also highlight a series of limitations associated with typical cost of basic needs approaches. Finally, we reaffirm that a 'sensibly eclectic' approach, employing multiple methods, is the best available mode for addressing these limitations.
Keywords: C13; I32; O12; 330; poverty measurement; utility consistency; cost of basic needs